PELATIHAN SISTEM BUKU BESAR DAN KERTAS KERJA PERUSAHAAN DAGANG BAGI SISWA/I SMA - Ekadjaja, Agustin; Kim Lie, Irene; Widjaja, Karen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Accounting as a business language has a strong role as a provision for someone to be able to become a reliable businessman. Learning accounting in order to form a strong foundation cannot be learned in an instant and must be learned in the long term like learning a language. One of the criteria needed to become a successful entrepreneur is to master the field of accounting including cash flow management, maintaining balance sheets, finding pathways to profitability as well as talking about money and planning for the future of the company. A successful company and business begins with the professionalism of the entrepreneur behind it who masters accounting well who can develop financial models and ensure success in business. General ledger is a journal or group of accounts that records transactions for a particular account in a broad picture and accounting working paper is a technique that can be used to assess the correctness of a financial statement produced. These two basic things are very important things to master in starting learning in accounting. The PKM team in this activity shared knowledge with the aim of equipping basic knowledge in accounting to students of High School. This activity was carried out face-to-face at High School which was attended by students of High School. Activities are packaged in the form of seminars and interactive discussions to introduce and provide training on basic accounting science in the preparation of accounting ledgers and working papers. We submit a report on the results of the implementation of this activity to LPPM Untar as a form of responsibility and output in this activity.